2012
DOI: 10.1590/s0100-204x2012000100014
|View full text |Cite
|
Sign up to set email alerts
|

Parâmetros sanguíneos, hepáticos e ruminais de ovinos alimentados com dietas com farelo de mamona destoxificado

Abstract: Resumo -O objetivo deste trabalho foi avaliar os parâmetros sanguíneos, hepáticos e ruminais, bem como caracterizar e quantificar a população de protozoários ciliados, no rúmen de ovinos alimentados com dietas com farelo de mamona destoxificada (FM). Foram utilizados 32 ovinos, para a avaliação dos parâmetros sanguíneos e hepáticos, e quatro ovinos adultos fistulados no rúmen, para a avaliação dos parâmetros ruminais. A dieta controle foi composta por feno de capim-buffel, milho em grão moído, ureia e farelo d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
2
2
0
Order By: Relevance
“…No significant changes in liver (protein, bilirubin, albumin and GOT) and kidney function metabolites (urea) were observed during the experimental period. Similar results were previously described for sheep (Menezes et al, 2012) and does (Silva et al, 2015) fed with diets containing detoxified castor meal. Thus, the results obtained in this study are within the reference range, which indicates that the experimental diets provide sufficient nutrients for the metabolic requirements of the animals.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…No significant changes in liver (protein, bilirubin, albumin and GOT) and kidney function metabolites (urea) were observed during the experimental period. Similar results were previously described for sheep (Menezes et al, 2012) and does (Silva et al, 2015) fed with diets containing detoxified castor meal. Thus, the results obtained in this study are within the reference range, which indicates that the experimental diets provide sufficient nutrients for the metabolic requirements of the animals.…”
Section: Resultssupporting
confidence: 90%
“…According to Vieira et al (2011), detoxified castor meal, when used for 70 days, improves the digestion in sheep in the finishing stages of production. Menezes et al (2012) did not observe alterations in the liver enzymes of sheep fed for 20 days with detoxified castor meal; in addition, replacing 45% of soy meal with detoxified castor meal improves the ruminal environment. In goats, non-detoxified castor de-oiled cake with ricin concentrations up to 50mg/kg of the residue may be used for long periods, at levels corresponding to 15% of the diet, completely substituting soybean cake, without compromising the meat traits (Silva et al, 2015).…”
Section: Introduction mentioning
confidence: 59%
“…Thus, the animals would need to intake more protein to meet their requirements. In this regard, Menezes et al (2012) reported a linear increase in the ammoniacal nitrogen concentration in the rumen fluid of sheep as SM was replaced by DCM in the same proportions used here, indicating an imbalance in the availability of energy and protein to microbial protein synthesis.…”
Section: Resultssupporting
confidence: 55%
“…The animals were fed twice a day at 0800 and 1600 hours. The chemical composition of feeds and diets are presented in Tables 1 and 2. The castor seed meal was purchased from Brasil Ecodiesel in Iraquara, BA, and transported to the Semiarid Embrapa, where it was detoxified with calcium hydroxide (Ca(OH) 2 ) diluted in water (9 L of water/kg of Ca(OH) 2 ), in a ratio of 60 g of Ca(OH) 2 per kilogram of castor seed meal (Menezes et al 2012). After detoxification, the material was placed in 200-L polyethylene containers for 24 h and then sun-dried for 12 h.…”
Section: Methodsmentioning
confidence: 99%